In Search of Living Knowledge - Swantz, Marja-Liisa (Book collections on Project MUSE., 2016)
Marja-Liisa Swantz has spent a lifetime conducting participatory action research in Tanzania, and In Search of Living Knowledge encapsulates her reactions. She started her career in 1952 in Tanganyika as an instructor to the first generation of women teachers at Ashira Teacher's Training College, situated on the slopes of Mount Kilimanjaro. In the first years of Tanzania's independence from Britain, she devoted five years (1965-1970) to participant research in a coastal Zaramo village near the capital city of Dar es Salaam. The research culminated in her book, Ritual and Symbol in Transitional Tanzanian Society, and a doctorate in Anthropology of Religion, which she received from the Swedish University of Uppsala in 1970. The author further developed the Participatory Approach to research while serving as a Senior Research Fellow at the University of Dar es Salaam from 1972 to 1975. After becoming a lecturer at the University of Helsinki she continued to develop Participatory Action Research with Tanzanian and Finnish doctoral candidates in a project in Bagamoyo, Tanzania, known as Jipemoyo. She continued to apply the participatory approach in research projects as Director of the Institute of Development Research at the University of Helsinki, where she taught anthropology, and as a Senior Researcher at the World Institute for Development Economics Research Institute in Helsinki in the 1980s. Since retirement, the author has continued her research, writing, and participation in development projects in Tanzania, including projects in Mtwara and Lindi from 1992 to 1998, and for 12 years while involved in a Local Government Cooperation project between Hartola in Finland and Iramba in Tanzania.